Violence, Stress, and Compromised Health - Frank Hutchins (Fundación Salud y Desarrollo Andino, Saludesa Ecuador, 2024)
The increase in violence in countries such as Ecuador, where organized crime, drugs, human smuggling, and political venality produce daily eruptions, has measurable consequences for human health. The skyrocketing homicide rate (from 7.7/100K in 2020 to 44.5 in 2023) (Statista 2024), along with increases in violent robberies, kidnapping, carjacking, and sexual assault, mean direct experiences with harm or death. Since 2021, over ten states of exception, and the existence of an "internal armed conflict," have been declared in Ecuador.